Hybrid Hashtags: #YouKnowYoureAKiwiWhen Your Tweet Contains Māori and English - Trye, David; Calude, Andreea S.; Bravo-Marquez, Felipe; Keegan, Te Taka (Frontiers in Artificial Intelligence, 2020)
Twitter constitutes a rich resource for investigating language contact phenomena. In this paper, we report findings from the analysis of a large-scale diachronic corpus of over one million tweets, containing loanwords from the indigenous language spoken in New Zealand, te reo Māori, into (NZ) English. Our analysis focuses on hashtags comprising mixed-language resources (which we term hybrid hashtags), bringing together descriptive linguistic tools (investigating length, word class and semantic domains of the hashtags) and quantitative methods (Random Forests and regression analysis). Our work has implications for language change and the study of loanwords (we argue that hybrid hashtags can be linked to loanword entrenchment), and for the study of language on social media (we challenge proposals of hashtags as “words”, and show that hashtags have a dual discourse role: a micro-function within the immediate linguistic context in which they occur and a macro-function, within the tweet as a whole).